First report of the land planarian Endeavouria septemlineata (Hyman, 1939) (Platyhelminthes, Tricladida, Continenticola, Geoplanidae) in French Polynesia - Justine, Jean-Lou; Lemarcis, Thomas; Gerlach, Justin; Winsor, Leigh (Zootaxa, 2018)
We report the presence of the land planarian Endeavouria septemlineata from Tahiti, French Polynesia, on the basis of a single specimen collected in 2017. Identification of the species was ascertained by external and internal morphology and DNA COI sequence. The finding is of importance for conservation, since this species is a predator of soil animals.